DIAGNÓSTICO E ACONSELHAMENTO TÉCNICO-GERENCIAL DE UMA UNIDADE DE PRODUÇÃO FAMILIAR GRÃOS/LEITE - Corrêa, Maira A.; Martins, Luciane R. V.; Uhde, Leonir T.; Basso, Nilvo; Henriques, Angélica d. O.; Kleemann, Ana P. H. (Salão do Conhecimento, 2013)
Resumo